Berquist's musculoskeletal imaging companion - Peterson, Jeffrey J. (Wolters Kluwer Health, 2018)
"Berquist's Musculoskeletal Imaging Companion is a practical quick-reference guide to the radiologic diagnosis of musculoskeletal disorders. It presents over 1500 large, clear images of common diseases, disorders, and injuries, accompanied by succinct, bulleted "key facts" about the clinical and imaging features of each condition. Chapters cover all anatomic regions and disease entities, imaging of orthopaedic appliances and prostheses, and detailed protocols for all current imaging modalities. The book demonstrates the utility of multiple modalities in specific situations and recommends the best, most cost-effective approach"--Provided by publisher.